Diskurssianalyysi Helsingin Sanomien Cambridge Analytica -skandaalin uutisoinnista - Maunu, Miikka Olavi (2024)
This master’s thesis examines Cambridge Analytica scandal and by using discourse analysis aims to find out how Helsingin Sanomat describes the scandal in its news articles and what kind of discourses emerges from those articles. The Cambridge Analytica scandal was disclosed in 2018 when leading news agencies around the world published news about it. In the center of the storm was a company called Cambridge Analytica which had collected and taken advantage of millions of users’ personal data.